2008
DOI: 10.1002/mrc.2320
|View full text |Cite
|
Sign up to set email alerts
|

A solid state and solution NMR study of the tautomerism in hydroxyquinoline carboxylic acids

Abstract: Some hydroxyquinoline carboxylic acids and their conjugate acids and bases were characterized by 13C and 15N NMR spectroscopy in solution and in the solid state. Differences in 13C and, in particular, 15N chemical shift patterns allow to distinguish between individual tautomers and confirm the presence of zwitterionic species in the solid state. Solution NMR spectra in dimethyl sulfoxide (DMSO) show effects resulting as a consequence of dynamic exchange and suggest the presence of an equilibrium mixture of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…Bond lengths (Å) donating and accepting sites between the pyridine and hydroxylic functions, mimicking previously described behaviors of some hydroxyquinoline carboxylic acids [10]. Compound 1a crystallises in space group Pbca (no.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Bond lengths (Å) donating and accepting sites between the pyridine and hydroxylic functions, mimicking previously described behaviors of some hydroxyquinoline carboxylic acids [10]. Compound 1a crystallises in space group Pbca (no.…”
Section: Resultsmentioning
confidence: 83%
“…The development of new and more efficient methodologies to transform hydroxyhaloquinolines to their derivatives which could help to look deeper into reasons of HIV inhibition is a subject of continuous interest in our laboratory [10,[13][14][15][16][17][18]. To understand their reactivity we compared selected geometric parameters such as bond lengths and bond angles presented on Tables 1-5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray crystal structure analysis showed the presence of hydrogen-bond donating and accepting sites between the pyridine and hydroxyl functional groups. We demonstrated by solution and solid state NMR studies [12] the neutral, cationic and anionic species of hydroxyquinoline carboxylic acids obtained by protonation or deprotonation existed a tautomeric equilibrium, which was evaluated by 13 C and 15 N chemical shifts. It has been shown that the analysis of 13 C and 15 N NMR spectra of hydroxyquinoline carboxylic acids gives insight into proton transfer reactions between the pyridine and carboxylic acid functional groups [12,33].…”
Section: Resultsmentioning
confidence: 99%